(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Floating tidal turbines offer the possibility of harvesting ocean energy in deep water and reducing costs of maintenance. However, suitable floating platforms need to be designed to be structurally reliable and facilitate the deployment of tidal energy devices. In this work, we propose a very large floating platform interconnected with mechanical hinges, as a foundation of a tidal turbine. As demonstrated in previous work by the authors, the hinge connections alleviate the structural loading of the platform. For the turbine, we consider a three bladed rotor and compute its average loads with a tidal open source blade element momentum solver. The performance of the platform is evaluated in the presence of the rotor. It is found that tidal turbine loading does not influence the motion of the platform significantly. The performance of the turbine is assessed by imposing sinusoidal flow velocities to the rotor to simulate the effect of heave and pitch motions of the platform. Results show that upstream of the platform, similar to a single body floater, tidal loads can increase significantly at low wave periods due to the motion of the platform. In contrast, downstream of the platform, the reduced range of motion of the platform is benign to the loading of the turbine. We also find that amplitude and phase of motion of the platform are key in tidal turbine performance, and under certain conditions, amplitude and phase can reduce tidal turbine loading with respect to a fixed turbine subject to wave loading. Hence, hinge connected platforms, can be used to provide load alleviation to both floating platform and tidal turbine.